Translation, Adaptation, and Psychometric Validation of the Indonesia Version of Job Diagnostic Survey: Hospital Nurse Setting - Aungsuroch, Yupin; Fisher, Mary L.; Juanamasta, I Gede; Wati, Ni Made Nopita; Lestari, R. Tri Rahyuning (Jurnal Keperawatan Soedirman, 2024)
A job diagnostic survey is used to measure work or job characteristics. However, there is limited study exploring the psychometric properties of the Indonesian version. This study aimed to validate the Indonesian version of the Hack and Oldham Job Diagnostic Survey. Cronbach's alpha coefficient value showed a significant value for all evaluated dimensions. As for concurrent validity, a significant correlation was discovered between all dimensions. Construct validity for job characteristics, experienced psychological states, and affective responses to the job were significant. Cronbach's alpha coefficient value was ≥0.825 for all evaluated dimensions. As for concurrent validity, a significant correlation was found between all dimensions (r = 0.357- 0.752). Construct validity for job characteristics, experienced psychological states, and affective responses to the job were significant (χ2 = 0.00, CFI = 0.99, GFI = 0.91, RMSEA = 0.06 and SRMSR = 0.05). The Job Diagnostic Survey Indonesian version (JDS-I) has been validated, exhibits good psychometric properties, and retains the original features of the instrument.